2016
DOI: 10.4103/0255-0857.174103
|View full text |Cite
|
Sign up to set email alerts
|

Virulence versus fitness determinants in Escherichia coli isolated from asymptomatic bacteriuria in healthy nonpregnant women

Abstract: The expression of adhesins, haemolysin, aerobactin, and capsule synthesis gene were similar in two groups suggesting their role as fitness factors. ABU isolates were better biofilm producers, reflecting its importance in silent persistence. Serum resistance gene which was more expressed in cystitis isolates may represent virulence determinant. Genetic makeup of E. coli does not change much rather genes helping in survival and colonisation are expressed equally in ABU and cystitis isolates as opposed to phenoty… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1

Citation Types

0
3
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 7 publications
(3 citation statements)
references
References 21 publications
0
3
0
Order By: Relevance
“…Cases of symptomatic UTI are treated using empirical antimicrobials; whereas it remains unwarranted in asymptomatic UTIs except conditions like pregnancy or before any invasive urologic procedure. Moreover, the asymptomatic bacteriuria has been treated depending on the phylogenetic group of the microbes, virulence genes involved, pathogenic island, properties of biofilm formation and iron transport mechanism as documented earlier [14–16]. As previous studies reported, evolution of pathogenic E.…”
Section: Resultsmentioning
confidence: 99%
“…Cases of symptomatic UTI are treated using empirical antimicrobials; whereas it remains unwarranted in asymptomatic UTIs except conditions like pregnancy or before any invasive urologic procedure. Moreover, the asymptomatic bacteriuria has been treated depending on the phylogenetic group of the microbes, virulence genes involved, pathogenic island, properties of biofilm formation and iron transport mechanism as documented earlier [14–16]. As previous studies reported, evolution of pathogenic E.…”
Section: Resultsmentioning
confidence: 99%
“…However, the virulence nature of these phylogroups can only be evaluated based on the occurrence of the virulence genes among the strains from these phylogroups. Among the mammalian hosts, the distribution of E. coli phylogroups was shown to be different and the probable reason for this was stated to be the environmental conditions such as host habitat, climate, diet, gut morphology, use of antimicrobial agents, and their effects on commensals in fecal flora [57]. The fecal flora which later colonizes the perineal and perianal area becomes the source of bacteria infecting or colonising the urinary tract, especially in females.…”
Section: Plos Onementioning
confidence: 99%
“…[1] The pathogenesis of UTI is complex and very often influenced by the host biological and behavioral factors as well as by virulence characteristics of the infecting uropathogen. [2] Members of the family Enterobacteriaceae are the most common organisms responsible for UTI. Escherichia coli is associated with nearly 80% of community-acquired and 50% of hospital-acquired UTIs.…”
Section: Introductionmentioning
confidence: 99%